2014
DOI: 10.1016/j.cmet.2014.08.001
|View full text |Cite
|
Sign up to set email alerts
|

A SIRT7-Dependent Acetylation Switch of GABPβ1 Controls Mitochondrial Function

Abstract: Mitochondrial activity is controlled by proteins encoded by both nuclear and mitochondrial DNA. Here, we identify Sirt7 as a crucial regulator of mitochondrial homeostasis. Sirt7 deficiency in mice induces multisystemic mitochondrial dysfunction, which is reflected by increased blood lactate levels, reduced exercise performance, cardiac dysfunction, hepatic microvesicular steatosis, and age-related hearing loss. This link between SIRT7 and mitochondrial function is translatable in humans, where SIRT7 overexpre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
257
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(272 citation statements)
references
References 49 publications
10
257
0
5
Order By: Relevance
“…Mitochondrial dysfunction and cardiac failure were recently described in aged Sirt7 −/− mice. 45 Loss of Sirt7 also results in increased p53 acetylation in the cardiomyocytes of aged Sirt7 −/− mice, 10 which enhances apoptosis and increases fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial dysfunction and cardiac failure were recently described in aged Sirt7 −/− mice. 45 Loss of Sirt7 also results in increased p53 acetylation in the cardiomyocytes of aged Sirt7 −/− mice, 10 which enhances apoptosis and increases fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Deficiency of SIRT7 has been linked to several pathologies including cardiac hypertrophy (Vakhrusheva et al , 2008b; Ryu et al , 2014), hepatic steatosis (Shin et al , 2013; Ryu et al , 2014), and deafness (Ryu et al , 2014). SIRT7 has been functionally linked to transcriptional regulation.…”
Section: Introductionmentioning
confidence: 99%
“…In their study, Sirt7 KO mice fed a chow diet develop fatty liver because of reduced suppression of ER stress [21]. Notably, however, the expression of ER stress-related genes was not increased in livers of our Sirt7 KO mice (unpublished data) or another line of Sirt7-deficient mice [22]. GA-binding protein (GABP) is a nuclear transcription factor that is important for mitochondrial biogenesis and function.…”
mentioning
confidence: 69%
“…Ryu et al found that SIRT7 deacetylates GABPb1, facilitating its transcriptional activation through complex formation with GABPa. They also reported that aged (42 weeks old) Sirt7 KO mice exhibit hepatic microvesicular steatosis because of mitochondrial dysfunction [22]. As we mainly examined young (11-17 weeks of age) Sirt7 KO mice fed an HFD, it is necessary to investigate hepatic lipid accumulation in aged Sirt7 KO mice.…”
mentioning
confidence: 99%